2018
DOI: 10.1007/s10815-018-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

Blastulation timing is associated with differential mitochondrial content in euploid embryos

Abstract: A lower MC at the blastocyst stage was associated with euploid status and blastocyst formation, indicating better embryo quality compared to those with a higher MC. Higher MC in aneuploid and arrested embryos may be explained by slower cell division or degradation of genomic DNA over time. Blastulation timing may be helpful for selection of higher quality embryos. Combining blastulation timing and MC along with morphologic grading and euploid status may offer a new direction in embryo selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In Experiment 2, we also found that supplementation with 100, 200 and 500 ng/mL PF4 increased the number of blastocysts at day 5 compared with the number observed in our conventional culture medium with BSA. This early blastocyst development may reflect a better embryo quality and a higher subsequent embryo developmental potential [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…In Experiment 2, we also found that supplementation with 100, 200 and 500 ng/mL PF4 increased the number of blastocysts at day 5 compared with the number observed in our conventional culture medium with BSA. This early blastocyst development may reflect a better embryo quality and a higher subsequent embryo developmental potential [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…Day-6 mtDNA content was lower in blastocysts when compared with arrested embryo. And embryos with longer blastulation time had higher mtDNA content (Ho et al, 2018). Moreover, human blastocyst after vitrification exhibited significant mtDNA replication after 5 h postwarm (Perez-Sanchez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These reports indicate that the differential mtDNA content between D-group and H-group blastocysts may be associated with different ICM and TE ratios. However, Ho et al [11] reported that the mtDNA copy number per cell obtained from biopsied TE was comparable to that obtained from whole embryos. Furthermore, another study [39] found that the mtDNA copy number did not differ between ICM and TE.…”
Section: Discussionmentioning
confidence: 97%
“…However, Ho et al . [ 11 ] reported that the mtDNA copy number per cell obtained from biopsied TE was comparable to that obtained from whole embryos. Furthermore, another study [ 39 ] found that the mtDNA copy number did not differ between ICM and TE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation